Quadupole Moments Calculation of Deformed Even-Even 156-170 Er Isotopes (Global Journal of Management and Business Research, 2014)
e have developed a special computing code for calculation of nuclear quadrupole moments versus deformation parameter β. For some even-even isotopes, it has been seen that by increasing neutron number, deformation parameter also increase, which means more deformation from spherical shape. even-even nuclei, quadrupole moment and deformation parameter.
Keywords: even-even nuclei; quadrupole moment and deformation parameter